Teaching English Prosodic Features to Nigerian Secondary School Pupils - Adegbite, W. (2014)
This study makes a case for the effective teaching of English prosodic features in Nigerian secondary schools and suggests ways by which the teaching can be carried out. It notes the importance of English prosody in promoting effective oral communication in the language and observes that this importance is not now usually well reflected in the teaching of English pronunciation to Nigerian learners. It thus believes that if the problems of teaching the prosodic features are identified and tackled, a better atmosphere will be created for the proper learning and use of English prosody in spoken English in Nigeria.